(untitled) (قضايا سياسية, 2023)
The Ukrainian crisis has repercussions not only for Russia and Ukraine but for all countries of the world, including the Middle East, at many levels, especially energy and food security. This has prompted Arab countries such as Algeria and Saudi Arabia to adapt to these repercussions through initiatives based on the strengthening of Arab regional national security, as reflected in the NATO initiative. Among these initiatives are the ones that seek to reconfigure regional security in accordance with the partnership with the major powers, whether in the realm of security or the economy.